2014
DOI: 10.1186/2193-1801-3-316
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating role of thymoquinone rich fractions from Nigella sativa oil and its constituents, thymoquinone and limonene on lipidemic-oxidative injury in rats

Abstract: Therapeutic role of Nigella sativa (NS) seed oil fractions, methanolic extract (ME) and volatile oil (VO) and their constituents, thymoquinone (TQ) and limonene (LMN) in relation to lipidemic-oxidative stress in Wistar rats was determined. The total phenolic contents of NS seed oil and their ME and VO extracts were 320.00 ± 3.00, 300.12 ± 0.04 and 288.41 ± 0.01 mg gallic acid equivalents per 100 g of NS oil, respectively. Their Fe+2 chelating activities were 870.00 ± 2.00, 222.31 ± 5.80 and 38.59 ± 1.43 mg EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…In addition, the present study found that HbA1c levels were significantly lower following the treatment of STZ-induced diabetic rats with TQ, while the levels of lipid peroxidase, NO, and TAC were better than untreated diabetic rats. These findings provide further confirmation of the potential beneficial effects of TQ on glycaemic control [55,56] and oxidative stress [57,58], despite the fact that most previous studies were mainly conducted using the plant N. sativa rather than the active ingredient TQ.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the present study found that HbA1c levels were significantly lower following the treatment of STZ-induced diabetic rats with TQ, while the levels of lipid peroxidase, NO, and TAC were better than untreated diabetic rats. These findings provide further confirmation of the potential beneficial effects of TQ on glycaemic control [55,56] and oxidative stress [57,58], despite the fact that most previous studies were mainly conducted using the plant N. sativa rather than the active ingredient TQ.…”
Section: Discussionsupporting
confidence: 66%
“…Thymol acts as a singlet oxygen quencher whereas thymoquinone and dithymoquinone have superoxide dismutase (SOD)-like activity and also act as free radical scavengers 27 - 29 . Oxidative stress causes endothelial dysfunction, leading to a reduction in the release or production of NO 30 - 32 , the proliferation of vascular smooth muscle cells and collagen deposition, which causes a thickening of the tunica media, and a narrowing of the vascular lumen 28 , which in turn impairs vasodilation 30 - 32 . Apart from its antioxidant properties, the blood pressure-lowering effect of N. sativa may be attributed to its diuretic properties 33 , its anti-inflammatory effect 34 or its reno-protective effect 35 .…”
Section: Discussionmentioning
confidence: 99%
“…All animal care and exploratory methods were in conformity with the guidelines of the Control and Supervision of Experiments on Animals (CPCSEA) and Institutional Animal Ethics Committee (IAEC), University of Allahabad, India (# IAEC/AU/2017(1)/011). The atherogenic suspension administrated to the rodents was fundamentally made out of 0.5% cholesterol, 3% coconut oil, and 0.25% cholic acid, and arranged by blending in a homogenizer. The measure of hesperidin supplementation was fundamentally settled based on accessible reports.…”
Section: Methodsmentioning
confidence: 99%